Variabilidade das temperaturas no leste do Estado do Paraná e sua associação com índices oceânicos - Marquetti , Jonathan Klein (2023)
The impacts of climate on society are mainly felt due to its extensive variations around its average, known as climate variability. As variability is inherent to the climate system, it is partially responsible for shaping the climatic conditions of a region. The primary cause of this variability process is the Sea Surface Anomalies (SSAs), which act as a major modulator of the global climate. The interaction between the ocean and the atmosphere generates pressure field variations, giving rise to the so-called "wave trains". Through teleconnections, these anomalies modify the climatic conditions in distant areas from their origin. The state of Paraná is in a region between the subtropics and has a significant relationship with different centers of action that cause regional climate variability, in association with SSAs. The ENSO (El Niño-Southern Oscillation) stands out in this process. The present research aims to understand the temporal variability of air temperature recorded in Paraná from 1925 to 2020. Data from meteorological stations in Curitiba, Castro, and Paranaguá/Morretes are used, along with indices developed for detecting climate anomalies in global SSAs, using statistical techniques, particularly the calculation of the linear correlation coefficient. The results indicate that the Pacific Ocean plays the primary role in modulating temperature indices in the study area, with the participation of ENSO and ODP indices. The analyzed stations exhibited different patterns among themselves, with Paranaguá and Curitiba showing more indices associated with the Atlantic compared to Castro. The Antarctic index showed a significant correlation with the FD2 index, indicating very cold days. The index related to the Indian Ocean showed significant correlation values with the stations, especially in heat indices such as SU30, TNx, and TR20. Overall, there was no general pattern for the three cities and fll indices; each one must be understood separately.